2006
DOI: 10.1038/sj.bmt.1705379
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-dose rasburicase (recombinant xanthine oxidase) in adult cancer patients with hyperuricemia

Abstract: Recombinant urate oxidase (rasburicase) lowers uric acid levels rapidly to very low levels at the labeled dose of 0.15-0.2 mg/kg daily for 5 days. Our past experience showed that a lower dose (3 mg) lowered uric acid levels sufficiently in most patients. A retrospective review was conducted to determine the effect of a fixed 3 mg dose of rasburicase in 43 adult patients with cancer undergoing hematopoietic stem cell transplantation or receiving chemotherapy who had elevated or rising uric acid levels (6.4-16.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 13 publications
4
66
0
1
Order By: Relevance
“…All patients demonstrated normalization of UA levels within 24 h of administration of rasburicase, without significant rebound of the UA ( Table 1). The patients also demonstrated improvement in serum creatinine and urinary output after treatment (Table 1), which is a finding consistent with those in previous studies [16][17][18][19][20][21][22]. Our study is, to our knowledge, the first reported use of rasburicase in hyperuricemic infants with renal failure.…”
Section: Discussionsupporting
confidence: 93%
“…All patients demonstrated normalization of UA levels within 24 h of administration of rasburicase, without significant rebound of the UA ( Table 1). The patients also demonstrated improvement in serum creatinine and urinary output after treatment (Table 1), which is a finding consistent with those in previous studies [16][17][18][19][20][21][22]. Our study is, to our knowledge, the first reported use of rasburicase in hyperuricemic infants with renal failure.…”
Section: Discussionsupporting
confidence: 93%
“…Limited experience suggests that lower doses of rUO are also effective at lowering uric acid levels [6,7]. When 7.5 mg/1V of rUO (0.14 mg/kg) was administered to our patient, his uric acid levels were sufficiently decreased.…”
Section: Chemosensitivementioning
confidence: 86%
“…[54][55][56][57] Alternative schedules of administration have been recently proposed; however, only a small fraction of the reported patients presented with metabolic abnormalities other than hyperuricemia, so more data are needed to support the possible use of these schedules even in overt TLS. 58,59 Studies comparing rasburicase with allopurinol in the treatment of pediatric patients with hyperuricemia due to TLS have shown better results with rasburicase. In a study by Bosly et al, 56 166 pediatric patients who had leukemia (74%), lymphoma (24%), or solid tumors (3%) were treated with rasburicase.…”
Section: Which Tumor Lysis Syndrome Therapy?mentioning
confidence: 99%